The Performance of Excellent Sectors for Economic Development in Morotai Island - Runtunuwu, Prince Charles Heston; Soamole, Bakri; Khotib, Muhammad (WELFARE Jurnal Ilmu Ekonomi, 2021)
This study aims to analyze the pattern of economic growth in Morotai Island. To find out the pattern of economic growth, an analysis of economic growth analysis, Location Quotient (LQ), Klassen Typology and Shift Share Analysis are used. The results showed that the pattern of economic growth in Morotai Island Regency from the year of 2010 to 2017 had a positive trend through the Klassen Typology analysis, although the GRDP growth rate and per capita income show a positive trend, but the increase is still below the national level so that Morotai Island Regency is in quadrant IV position (the category of regions is relatively underdeveloped), Based on LQ analysis, four leading sectors were obtained, which are the base sectors ofÂ  Morotai Island Regency in 2017 Based on the shift share analysis, the sectors that had the highest national share were agriculture, forestry and fisheries. The negative proportional shift value indicates that although it has a positive trend, the growth rate is slower compared to North Maluku.Â  The projected results show that economic growth from 2017 will increase by 24.06 percent in 2019, it is hoped that the Regional Government can increase economic growth by giving special attention to leading sectors that have the potential to increase economic growth.Penelitian ini bertujuan untuk menganalisis pola pertumbuhan ekonomi di Kabupaten Pulau Morotai dan untuk mengetahui pola pertumbuhan ekonomi,digunakan beberapa analisa yaitu Pertumbuhan Ekonomi, Location Quotient (LQ), Tipologi Klassen dan Analisis Shift Share. Hasil penelitian menunjukkan bahwa pola pertumbuhan ekonomi Kabupaten Pulau Morotai Tahun 2010 hingga tahun 2017 memiliki tren positif. Melalui analisis Tipologi Klassen, meskipun laju pertumbuhan PDRB dan pendapatan perkapita menunjukkan tren positif, namun peningkatannya masih di bawah nasional sehingga menempatkan Kabupaten Pulau Morotai berada pada posisi kuadran IV (kategori daerah relatif tertinggal). Dengan analisis LQ Diperoleh 4 sektor unggulan yang merupakan sektor basis Kabupaten Pulau Morotai Tahun 2017. Berdasarkan analisis shift share, sektor yang memiliki national share tertinggi adalah sektor pertanian, kehutanan dan perikanan. Nilai proportional shift yang negatif, menunjukkan bahwa meskipun memiliki tren positif namun tingkat pertumbuhan lebih lambat dibandingkan dengan Provinsi Maluku Utara. Hasil proyeksi menunjukkan bahwa pertumbuhan ekonomi dari tahun 2017 akan meningkat sebesar 24,06 persen pada tahun 2019. Diharapkan pemerintah daerah dapat meningkatkan pertumbuhan ekonomi dengan memberikan perhatian khusus pada sektor-sektor unggulan yang berpotensi meningkatkan pertumbuhan ekonomi.